Fungicidal activity of Eucalyptus tereticornis essential oil on the pathogenic fungus Fusarium oxysporum (2011)
ABSTRACT: The objective of present paper was to determine the antifungal activity of the Eucalyptus tereticornis (Myrtaceae) essential oil and two fractions on the Fusarium oxysporum mushroom, a pathogen with clinical and agricultural significance. The total citronelal (44.8 %) and geraniol (9.78 %) essential oil had a fungicidal effect at a 3 g/L concentration and a fungicidal activity at small concentrations. The A and B fractions composed most of p-mentane-3,8-diol (18.95 %) and geraniol acetate (24.34 %), respectively were more active than the total extract. The observations at microscopic level showed damages and changes in hyphae and chlamydospores, as well as a decrease in the number of conidia. The observed fungicidal activity and the morphologic damages were dependent on the concentration.